Uveitis in Patients Treated with CTLA-4 and PD-1 Checkpoint Blockade Inhibition. (17th February 2020) - Sun, Michel M.; Levinson, Ralph D.; Filipowicz, Artur; Anesi, Stephen; Kaplan, Henry J.; Wang, Wei; Goldstein, Debra A.; Gangaputra, Sapna; Swan, Robert T.; Sen, H. Nida; Gordon, Lynn K.
ABSTRACT: Purpose : To investigate the link between treatment with CTLA-4 and PD-1 checkpoint blockade inhibitors and the development of noninfectious uveitis. Methods : A survey was distributed to uveitis specialists to identify patients who developed uveitis while receiving either PD-1 inhibitors pembrolizumab and nivolumab; PD-L1 inhibitors atezolizumab, avelumab, and durvalumab; or the CTLA-4 inhibitor ipilimumab. Results : Fifteen patients from seven institutions were identified. The most common cancer diagnosis (13/15) was malignant melanoma. Fourteen patients had a new uveitis diagnosis following checkpoint blockade administration (six anterior uveitis, six panuveitis, one posterior uveitis, one anterior/intermediate combined); one patient developed optic neuritis. Uveitis was diagnosed within 6 months after drug initiation for 11/12 patients (median 63 days). Corticosteroid treatment was effective for most patients, although two patients had permanent loss of vision. Conclusions : Patients on checkpoint inhibitor therapy should be educated to seek care if they develop ocular symptoms, and prompt referral to specialists should be incorporated into oncology protocols.